Wage Growth, Landholding, and Mechanization in Chinese Agriculture - Wang, Xiaobing (World Bank Group, Washington, DC, 2015)
This paper uses farm panel data from China to examine the dynamics of land transactions, machine investments, and the demand for machine services. Recently, China's agriculture has experienced a large expansion of machine rentals and machine services provided by specialized agents, which has contributed to mechanization of agricultural production. The empirical results show that an increase in nonagricultural wage rates leads to expansion of self-cultivated land size. A rise in the proportion of nonagricultural income or the migration rate also increases the size of self-cultivated land. Interestingly, however, relatively educated farm households decrease the size of self-cultivated land, which suggests that relatively less educated farmers tend to specialize in farming. The demand for machine services has also increased if agricultural wage and migration rate increased over time, especially among relatively large farms. The results on crop income support the complementarity between rented-in land and machine services (demanded), which implies that scale economies are arising in Chinese agriculture with mechanization and active land rental markets.